The remains of the day: neuropsychological findings in postacute transient global amnesia: original communication - Sandikci, Vesile; Ebert, Anne; Zurwesten, Lea; Platten, Michael; Szabo, Kristina; Hoyer, Carolin (Journal of neurology, 2022)
Current clinical diagnostic criteria of transient global amnesia (TGA) require the episode to completely resolve within 24 h. Small case series investigating the neuropsychological profiles obtained during the first days after TGA are inconclusive, with some suggesting the persistence of memory deficits.